Factors associated with mood disorders and the efficacy of the targeted treatment of functional dyspepsia: A randomized clinical trial - Huang, Qian; Zheng, Shaopeng; Cai, Ting; Zhang, Suxin; Su, Qian; Wang, Fen (Frontiers in Medicine, 2022)
Background: Patients with functional dyspepsia (FD) are often accompanied by mood disorders (MDs). This study aimed to identify factors associated with MDs in patients with FD and the efficacy of targeted treatment plans. Methods: Patients with FD having MDs and acid reflux were treated with flupentixol and melitracen (FM) and acid-suppressive therapy (AST) (H2 receptor antagonists (H2RAs) (group A) or proton pump inhibitors (PPIs) (group B)), and those without acid reflux (group C) did not receive AST. Patients with FD without MDs were randomly administered H2RAs (group D) or PPIs (group E). The primary endpoints were factors associated with MDs and improvement in gastrointestinal (GI) symptoms and MDs. Results: Among the 362 patients with FD enrolled, those having high GI scores and low education were found prone to MDs. At week 2, the remission rate of overall GI symptoms and depression was significantly higher in group B than that in groups A and C (GI: 72.72% [32/44] vs. 47.73% [21/44] and 72.72% [32/44] vs. 38.94% [44/113], all P < 0.05; depression: 72.22% [26/36] vs. 41.67% [15/36] and 72.22% [26/36] vs. 41.57% [37/89], all P < 0.05). Furthermore, the remission rate of overall GI symptoms was significantly higher in group E than that in group D (60.29% [41/68] vs. 42.65% [29/68], P < 0.05). At week 8, similar efficacies and adverse reactions were observed in these groups. Conclusion: The risk factors for MDs were high GI scores and low literacy. Thus, targeted treatment can improve the efficacy of patients with FD.